The grey side of hibah amanah as instrument of property management in Malaysia - Zul Kepli, Mohd Yazid; Ahmad Bustami, Tajul Aris (2018)
The widespread use of hibah amanah can be seen as big players including the Amanah Raya Berhad (ARB), Amanah Saham Nasional Bhd (ASNB), Tabung Haji (TH),Wasiyyah Shoppe Berhad, as-Salihin Trustee Berhad, CIMB, and Prudential BSN Takaful Berhad decide to embrace it. It has become a popular alternative to the Islamic system of inheritance (faraid) as it enables a donor to have full control during the donor’s life over his/her property while the beneficiary can only benefit from it upon the death of the donor. It enables the donor to disregard the usual limitations provided under the faraid since endowment of hibah amanah is arguably not subjected to faraid law. This article starts with analysis on the shariah perspective of hibah amanah, focusing on the arguments forwarded by scholars that support and oppose hibah amanah, together with their justifications from the Quran, Sunnah and other basis of their view (ijtihad). This is a qualitative study using content analysis methodology. This article attempts to clarify and describe the general characteristics and legal requirements for hibah amanah to be valid in Malaysia. This article also highlights the long list of problems and challenges related to hibah amanah especially from the shariah, economic and legal perspectives. This article reveals that despite the sudden widespread and popular use of hibah amanah as an instrument of property management, there are many legal complications and obstacles that will appear. This article stresses the importance of having a clear legal and regulatory mechanism to address all issues related to hibah amanah.